Unilateral Absence of Ovary and Fallopian Tube: 3 Rare Case Reports (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Here we reported three cases of unilateral tubal and ovarian absence, along with laparoscopic images and images during ceasarean section in Anwer Khan Modern Medical College. Three patients with primary infertility of 6-8 years duration were reported as non-visualization of right adnexal structures on transvaginal ultrasound and hysterosalpingography. Absence of right adnexal structures of varying degree were detected during laparoscopy. Subsequent evaluation of renal system with Intravenous Pyelography were done. Ipsilateral absence of the fallopian tube and ovary without any other system anomalies were detected. Vascular accidents, Congenital defects or torsion could be the possible etiologic factors. Laparoscopy is a feasible option as a diagnostic tool for these cases.Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 97-100